Effect of aging and finish machining on the surface integrity of selective laser melted maraging steel - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2021)
Purpose The present study aims to investigate the effect of finish machining and aging processes on the surface integrity of the selective laser melted (SLM) maraging steel samples and compared them with those obtained conventionally. Design/methodology/approach Finish machining and aging were applied on the SLM and wrought maraging samples to investigate and compare their microstructural and mechanical properties such as surface roughness, microhardness and wear resistance. Findings After applying aging and finish machining treatments, the surface roughness <1 mu m, microhardness (542Hv) and wear resistance (COF 0.578) of SLM samples were similar to their wrought counterparts. Compared to finish machining, the effect of aging was more significant on the microhardness and the wear resistance, regardless of sample type. Originality/value The knowledge of post-processing is essential to enhance the functional performance of the SLM samples. Aging and finish machining were applied for the first time to evaluate the surface integrity of the SLM prepared maraging steel and compared it with the wrought samples.
Keywords: Wear resistance; Finish machining; Heat treatment; Selective laser melting; Additive manufacturing; Powder bed fusion; Maraging steel; Aging; MECHANICAL-PROPERTIES; MICROSTRUCTURAL EVOLUTION; TEMPERATURE; BEHAVIOR; PARTS; PRECIPITATION; RESISTANCE; STRENGTH